Trust, communication and contracts: Experimental evidence - Avner Ben-Ner; Louis Putterman (Brown University, Department of Economics, 2006)
We introduce opportunities for pre-play communication and to enter binding or non-binding contracts in trust games, and find (a) communication increases trusting and trustworthiness, (b) contracts are unnecessary for trusting and trustworthy behaviors and are eschewed by many players, (c) more trusting leads to higher earnings, and (d) both trustors and trustees favor “fair and efficient” proposals over the unequal proposals predicted by theory.
Keywords: C72; C91; D63; 330; trust game; trust; trustworthiness; reciprocity; Commitment; communication; Vertrauen; Spieltheorie